Facial skin mapping: from single point bio‐instrumental evaluation to continuous visualization of skin hydration, barrier function, skin surface pH, and sebum in different ethnic skin types. (30th August 2019) - Voegeli, R.; Gierschendorf, J.; Summers, B.; Rawlings, A. V.
Abstract: Dry skin is one of the most important concerns of consumers worldwide. Despite huge efforts over several decades, the personal care industry still does not offer a perfect solution to satisfy the unmet needs of consumers for moisturising treatments in different ethnic groups. The paucity of data for the underlying cellular and biochemical problems in, and the effects of moisturisers on photodamaged facial skin may partly explain this. Mainly, single point measurements are used to understand the effects of products on skin physiology even on surrogate skin sites such as the non‐photodamaged volar forearm. Some groups have developed discontinuous facial maps of skin biophysical properties, however, in 2014 a continuous facial analysis of bio‐instrumental evaluations was developed using a heat map approach. These maps enabled a continuous visualization of features that not only revealed an unexpected complexity of facial skin but also indicated that use of surrogate skin sites for facial skin is inappropriate. We have demonstrated that remarkable gradients of skin hydration, TEWL, skin surface pH and sebum exist within short distances across the face and the gradients are distinctive among different ethnic groups. In addition, these studies have demonstrated that darkly‐pigmented individuals do not necessarily have a better skin barrier function than their less‐pigmented counterparts and that Caucasians have a lower facial skin surface pH compared with more pigmented subjects. Overall, there are no correlations between capacitance, TEWL and skin surface pH including individual topology angle values. Novel 3D camera approaches have also been used to facilitate a more precise assignment of measurement sites and visualisation. The 3D facial colour mappings illustrated precisely the local moisturising effects of a moisturising cream. There were subtle ethnic differences in efficacy that may be related to underlying skin biochemistry and/or ethnic differences in product application. A placebo‐controlled study using conductance measurements in Chinese subjects is also reported. Finally, a new whole face statistical approach has been taken to prove differences in skin parameters but also of moisturiser treatment that adds further to our understanding of the ethnic differences in skin physiology and product application. This paper reviews the background of the development and application of this methodology. Abstract : The skin mapping technology enables the transformation of bio‐instrumental data to continuous 2D and 3D visualisation of facial skin features. This approach reveals the complexity of facial skin and the differences of differently pigmented skin types. Résumé: L'assèchement de la peau est l'un des problèmes les plus importants chez les consommateurs à travers le monde. En dépit des efforts fournis dans les dernières décennies, l'industrie du soin ne propose pas encore une solution parfaite qui répond aux attentes des consommateurs de différentes ethnies pour des traitements hydratants. Le manque de données concernant les problèmes de mécanisme cellulaire et biochimique, ainsi que les effets des soins hydratants sur la peau du visage photo‐endommagée peuvent en partie expliquer cela. En général, une mesure ponctuelle est réalisée pour comprendre les effets des produits sur la physiologie de la peau sur des sites de substitution tels que l'avant‐bras non photo‐endommagé. Certains groupes ont développé des cartographies du visages discontinues des propriétés biophysiques de la peau, mais ce n'est qu'en 2014 qu'une analyse continue du visage de l'évaluation bio‐instrumentale a été proposée en utilisant une approche par cartographie de chaleur. Ces cartographies permettent une visualisation continue des caractéristiques qui ne révèlent pas seulement une complexité inattendue de la peau du visage mais indique également que l'utilisation de sites de substitution est inappropriée. Nous avons démontré que certains gradients liés à l'hydratation de la peau, à la PIE, au pH à la surface de la peau et au sébum sont présents sur de faibles distances à travers le visage et que ces gradients sont différents selon les groupes ethniques. De plus, ces études ont démontré que les individus ayant une pigmentation de peau importante n'ont pas nécessairement une meilleure fonction de barrière cutanée que leurs homologues ayant une peau moins pigmentée et que les Caucasiens ont une plus faible surface de pH sur le bas du visage en comparaison avec des sujets ayant plus de pigmentation. Globalement, en incluant les aspects typologiques individuels, il n'y a pas de corrélation entre la capacitance, la PIE et le pH à la surface de la peau. Une nouvelle approche par caméra 3D à également été utilisée pour faciliter l'attribution et la visualisation plus précise de la mesure par site. Les cartographies du visage 3D en couleur illustrent précisément les effets hydratants localisés d'une crème hydratante. Il y avait des différences ethniques subtiles dans l'efficacité qui peuvent être liées au mécanisme de la biochimie cutanée et/ou dans l'application des produits des différentes ethnies. Une étude contrôlée par placebo utilisant une mesure de conductance chez les sujets d'origine chinoise est également communiquée. Enfin, une nouvelle approche statistique sur le visage complet a été adoptée afin de prouver les différences dans les paramètres de la peau mais aussi dans le traitement hydratant, ce qui nous permet de mieux comprendre les différences ethniques dans la physiologie de la peau et l'application des produits. Cette publication retrace les éléments de développement ainsi que l'application des méthodologies.